PENGARUH SUPERVISI AKADEMIK PENGAWAS SEKOLAH, KEPEMIMPINAN KEPALA SEKOLAH, DAN MOTIVASI BERPRESTASI TERHADAP KINERJA GURU SEKOLAH DASAR - Sukamto, Sukamto; Rasiman, Rasiman; Muhtarom, Muhtarom (LPPM Institut Pendidikan Nusantara Global, 2023)
Performance is very important in determining the quality of a person's work, including a teacher. Teacher performance is an important factor in determining the quality of education in a school. There are many factors that can influence teacher performance, including the academic supervision of school supervisors, the leadership of the school principal, and teacher achievement motivation. This research aims to determine the academic supervision of school supervisors, the leadership of school principals, and teacher achievement motivation on teacher performance. This research is correlational research with a quantitative approach. The research population was State Elementary School teachers in the Target Area 2, Kembang District, Jepara Regency. Sampling used a total sampling technique with a total sample of 77 teachers. The data collection method uses a questionnaire. Data analysis techniques use descriptive analysis and multiple linear regression analysis. The results of the research show that: (1) the school supervisor's academic supervision has an effect on teacher performance by 13.9%, (2) the principal's leadership has an effect on teacher performance by 12.3%, (3) achievement motivation has an effect on teacher performance by 35,5%, (4) school supervisor academic supervision, principal leadership, and achievement motivation together influence the principal's performance by 61.7%.